Az útbaigazított emlékezet Kazinczynál: Identitásminták Kazinczy önéletrajzi szöveghálózatában – a kulturális emlékezethely gondolatának megjelenése - Orbán, László (Studia Litteraria, 2012)
Történetek’ Kalendarioma is one of the most exciting recollective texts by Kazinczy. This is, in fact, a diary of anniversaries, constructed from short memos and notes, in which personal, cultural and historical events are mixed. The text’s structure is formalized by the dates, thus personal memories, cultural and community events, feasts and anniversaries are randomly juxtaposed. The construction of these notes into stories can often be observed in Kazinczy’s autobiographical texts, so the separate personal and public notes of Történetek’ Kalendarioma are arranged in one narrative. This is how a piece of personal memory related to Mohács – the memory of a lunch or an itinerary – and the historical thinking related to Mohács become constitutive parts of Kazinczy’s identity. Kalendariom provides a sketch of a rather complex personality, which is built up from elements of national and religious history, family traditions and narratives of personal memories. Történetek Kalendarioma’ is the formalized map of Kazinczy’s own knowledge-network, a collection of identity samples, a catalog of roles. All in all: a version of Kazinczy’s identity.